A single-center, retrospective study-spring-evaluating the efficacy and safety of recombinant human vascular endothelial inhibitor combined with anti-PD-1 in elderly patients aged 80 and above with NSCLC - Xing, Tian; Gao, Qianqian; Zhu, Hongbin; Gao, Jianrong; Yan, Ganglin (Frontiers in Immunology, 2024)
Aim: To investigate the efficacy and safety of combining Recombinant Human Endostatin Injection (marketed as Endo) with anti-PD-1 in elderly patients aged 80 and above with non-small cell lung cancer (NSCLC).Methods: Retrospective analysis of 181 patients with NSCLC aged 80 and above treated in the Department of Respiratory and Critical Care Medicine at Chaohu Hospital, affiliated with Anhui Medical University, from June 2019 to January 2024. Patients who received at least one cycle of combined Endo with anti-PD-1 were included based on inclusion criteria. Clinical and pathological data were collected, including complete blood count, liver and kidney function, electrocardiogram, coagulation function, thyroid function, cardiac enzymes, and whole-body imaging. Adverse events were recorded with a final follow-up on January 25, 2024. The primary endpoints were progressionfree survival (PFS) and overall survival (OS), with safety as a secondary endpoint.Results: This study involved 14 elderly patients with NSCLC aged over 80. Median progression-free survival (mPFS) was 102 days, and median overall survival (mOS) was 311 days. Subgroup analyses based on treatment cycles showed a non-significant 441-day mPFS increase in the long-term group (≥ 6 cycles, 5 patients) compared to the short-term group (<6 cycles, 9 patients). However, the mOS in the long-term group significantly exceeded the short-term group by 141 days, with statistical significance (P=0.048). Further categorization revealed a 204-day shorter mPFS in the monotherapy maintenance group (Endo or Immunol) compared to the combination maintenance group (Endo combined with Immunol, 441 days). The mOS of the monotherapy maintenance group was longer (686 days) than the combination maintenance group (311 days), but no statistical significance (P= 0.710, 0.920). Throughout the treatment, 77 adverse events were recorded, mainly grade 1-2, with no new treatment-related reactions occurred. Overall, the safety of Endo combined with anti-PD-1 was considered good and manageable.The combination of Endo and anti-PD-1 could be an effective treatment choice for patients with NSCLC aged 80 and above.